A systematic literature review on developing students’ mathematicalcommunication skills - Fitriasari, Putri; Juandi, Dadang; Nurlaelah, Elah; Balkist, Pujia Siti (Jurnal Pendidikan Matematika RAFA, 2024)
This study aims to reveal the analysis of previously published articles based on the PRISMA procedure that guides researchers' self-directed learning on online platforms through a search conducted on the ERIC database with general keywords such as mathematical communication skills’ and related terms. This review exhibits exclusion criteria in the publication distribution. Whilst, all included documents are articles in English language. The distribution of articles published specifically by years and full text available. The varied of findings show ERIC database provides essential information pertaining to mathematical communication and approach carried out involving students from various level. Meanwhile, developing student’s mathematical communication using student-centered teaching methods is one of the effective strategies.